Hubungan Kontrol Diri dan Gaya Hidup Hedonis dengan Perilaku Konsumtif Terhadap Produk Fashion Pada Mahasiswa Laki-Laki Di Yogyakarta - Delonix Regia Pawestri; Annisa Warastri (Dinasti Research, 2024)
This study aims to analyze the relation of self-control and hedonistic lifestyle on the consumptive behavior of male students in Yogyakarta, with a specific focus on expenditures for fashion products. A quantitative approach was employed, involving 103 respondents. The findings reveal that students allocate up to 50% of their allowance to fashion, influenced by trends and advertisements, despite the majority exhibiting high levels of self-control. Regression analysis indicates that self-control negatively affects consumptive behavior, while hedonistic lifestyle positively influences it. The coefficient of determination (R²) shows that 61.6% of the variation in consumptive behavior can be explained by these two variables. These results underscore the importance of self-control in managing expenditures and highlight the negative impact of a hedonistic lifestyle on consumptive behavior. This research is expected to provide deeper insights into the relationship between self-control, hedonistic lifestyle, and consumptive behavior among students, serving as a reference for more prudent financial management.